2021
DOI: 10.1111/pace.14287
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation associated with implantable electrical device insertion: A systematic review and meta‐analysis

Abstract: Background Implantable cardioverter defibrillator (ICD) and permanent pacemaker (PPM) lead placement may worsen or result in tricuspid regurgitation (TR). While the association between lead placement and the incidence of TR has been established, current understanding of this problem remains incomplete. This systematic review and meta‐analysis sought to pool the existing evidence to better understand the occurrence and severity of TR associated with cardiac implantable electrical device (CIED) insertion. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In the 1970s, postmortem investigations demonstrated that pacemaker leads can adhere to the TV leaflets or the papillary muscles (Gibson et al, 1980 ). In chronic TR, a number of studies have demonstrated that adhesion of TV leaflet to the pacing lead results in restricted movement, causing an abnormal coaptation of the posterior leaflet with the anterior and septal leaflets (Addetia et al, 2019 ; Tatum et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, postmortem investigations demonstrated that pacemaker leads can adhere to the TV leaflets or the papillary muscles (Gibson et al, 1980 ). In chronic TR, a number of studies have demonstrated that adhesion of TV leaflet to the pacing lead results in restricted movement, causing an abnormal coaptation of the posterior leaflet with the anterior and septal leaflets (Addetia et al, 2019 ; Tatum et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3] Meanwhile, the transvalvular lead of the ICD may generate additional weight and rigidity to the tricuspid valve due to its calibre. [10] Our findings revealed that preimplantation atrial fi brillation was involved in the presence of post-implantation TR. Some studies have reported that atrial fibrillation is associated with annular dilation and results in TR even in the absence of device leads.…”
Section: Discussionmentioning
confidence: 51%
“… 56 Tatum et al . 57 reported that lead placement is associated with post-procedural TR worsening in 20% of the patients with a total prevalence of at least moderate TR in 41%.…”
Section: Definition and Terminologymentioning
confidence: 99%